Resistance of potato cultivars and hybrid clones from the VIR collection to the northwestern population of Phytophthora infestans - N. M. Zoteyeva; O. S. Kosareva; E. V. Rogozina; N. A. Chalaya (Труды по прикладной ботанике, генетике и селекции)
Background. Phytophthora infestans (Mont.) de Bary is a well-known pathogen affecting potato plants. Due to the changes in the pathogen population, the late blight disease caused by P. infestans is still difficult to manage. Economic losses are caused by the susceptibility of potato foliage or tubers to late blight, and both expressions of susceptibility are often not interconnected. Potato cultivars resistant to P. infestans are still too few to ensure reduction of harvest losses.   Material and methods. In total, 682 potato cultivars and 20 hybrid clones from the VIR collection were screened in field and laboratory tests. They were assessed by conventional techniques. A score scale of 1–9 points was used both in the field and the laboratory, with 9 corresponding to disease resistance.   Results. The results showed high infection pressure in the field during all four growing seasons of the experiment. The degrees of damage on the foliage varied from 1 to 8 points. The percentage of cultivars with strongly damaged foliage ranged from 55 % in 2020 to 66 % in 2023. From 17 % to 23 % of cultivars were assessed as moderately susceptible. The fact that many cultivars of various origin manifested compatibility with the local population of P. infestans during four growing seasons confirms its high and stable pathogenicity. Cultivars with high (points 7–8) or moderate (point 6) resistance were identified across the four years of testing. The part of the cultivars recognized as resistant earlier in 2017–2019 appeared to be moderately resistant or moderately susceptible in 2020–2023. Laboratory tests succeeded to identify genotypes with tuber resistance to late blight.